The Effects of Collaborative Text Reconstruction on Form 4 Pupils’ Narrative Writing - Yuan, Ting Sie; Mohamad, Maslawati (Opción, 2019)
This case study aimed to explore the effects of collaborative text reconstruction on rural secondary pupils’ narrative writing. The research instruments were document analysis, focus group interview, and field notes. The participants were six low English proficiency Form 4 pupils in a rural school located in Sarawak. The data were analysed by applying thematic analysis. The results showed that collaborative text reconstruction enhances the participants’ grammar, vocabulary, and content in narrative writing. Participants found that collaborative text reconstruction as one of the most interesting activity to learn narrative writing.